2014
DOI: 10.2298/fil1407381m
|View full text |Cite
|
Sign up to set email alerts
|

New type of generalized difference sequence space of non-absolute type and some matrix transformations

Abstract: In the present paper, we introduce a new difference sequence space rqB(u,p) by using the Riesz mean and the B-difference matrix. We show rqB(u,p) is a complete linear metric space and is linearly isomorphic to the space l(p). We have also computed its ?-, ?- and ?-duals. Furthermore, we have constructed the basis of rqB(u,p) and characterize a matrix class (rqB(u, p), l?).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In recent years, some researchers have addressed the approach to constructing a new sequence space by means of the matrix domain of a particular limitation method; see, for instance, [3,4,7,31] and the references therein. In [23], the author has studied the following difference sequence space…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some researchers have addressed the approach to constructing a new sequence space by means of the matrix domain of a particular limitation method; see, for instance, [3,4,7,31] and the references therein. In [23], the author has studied the following difference sequence space…”
Section: Introductionmentioning
confidence: 99%
“…We call a space Y to be FK space if it is a complete metric space with continuous coordinated p r : Y → C where p r (u) = u r for all u ∈ Y and r ∈ N. A normed FK space is called a BK space as defined in [16,23] and etc.…”
Section: Introductionmentioning
confidence: 99%
“…Some definitions of non-integral derivatives have been generalized by using techniques of new difference sequence spaces of non-integral order as can be seen in [3,19] etc. To establish a new space with the help of matrix methods were studied by several authors as can be found in [1,[11][12][13][14][15][16][17], [23][24][25][26][27][28][29][30][31]33] and many more. Following the references cited, the scenario here is to put forward and synthesis the spaces R q ( p g , κ) of order κ (non-integral) for which ∆…”
Section: Introductionmentioning
confidence: 99%